Myh deficiency enhances intestinal tumorigenesis in multiple intestinal neoplasia (ApcMin/+) mice. - Sieber, O; Howarth, K; Thirlwell, C; Rowan, A; Mandir, N; Goodlad, R; Gilkar, A; Spencer-Dene, B; Stamp, G; Johnson, V; Silver, A; Yang, H; et al. (2004)
Monoallelic APC and biallelic MYH (homolog of Escherichia coli mutY) germ-line mutations are independently associated with a strong predisposition to colorectal adenomas and carcinoma in humans. Whereas mice heterozygous for mutant Apc develop intestinal tumors, mice homozygous for mutant Myh do not show increased tumor susceptibility. We analyzed the phenotype of Apc(Min/+)/Myh(-/-) mice and found that they developed significantly more adenomas in the small intestine than did Apc(Min/+)/Myh(+/+) or Apc(Min/+)/Myh(+/-) mice (median 231 versus 151 versus 152). In the large bowel, Apc(Min/+)/Myh(-/-) mice showed significant increases in the number of aberrant crypt foci. In addition, Apc(Min/+)/Myh(-/-) mice developed an increased number of mammary tumors. Molecular analyses suggested that at least 19% of intestinal tumors from Apc(Min/+)/Myh(-/-) mice had acquired intragenic Apc mutations rather than allelic loss. Consistent with a defect in base excision repair, three intragenic Apc mutations in polyps without allelic loss from Apc(Min/+)/Myh(-/-) mice were shown to be G:C to T:A transversions which resulted in termination codons; no such mutations were found in polyps from Apc(Min/+)/Myh(+/+) or Apc(Min/+)/Myh(+/-) mice. Tumors from Apc(Min/+)/Myh(+/-) mice harbored neither somatic mutations nor allelic loss at Myh. Thus, homozygous, but not heterozygous, Myh deficiency enhanced intestinal tumorigenesis in Apc(Min/+) mice. The excess small-bowel adenomas in Apc(Min/+)/Myh(-/-) mice, therefore, appear to be a model of MYH-associated polyposis in humans.